Hormonal Alterations in Individuals with Obesity After Metabolic Bariatric Surgery: A Narrative Review - Anastasiou, Ioanna A; Kounatidis, Dimitris; Rebelos, Eleni; Vallianou, Natalia G; Tentolouris, Anastasios; Tentolouris, Nikolaos; Dalamaga, Maria; Karampela, Irene (MDPI, 2026)
The gastrointestinal (GI) tract is increasingly recognized as an important regulator of energy balance and metabolism, extending beyond its traditional digestive functions. This review synthesizes current research on how modifications to the GI tract, particularly those induced by metabolic bariatric surgery (MBS), influence hormonal and physiological processes involved in glucose regulation and appetite control. MBS procedures, such as Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG), induce significant and sustained weight loss, but also elicit adaptive morphological and functional changes within the intestines. These alterations include intestinal hypertrophy, increased mucosal surface area, changes in nutrient transit time, and modifications in enzyme activity. Such changes enhance the secretion of key gut hormones, including glucagon-like peptide 1 (GLP-1) and peptide YY (PYY), which play vital roles in promoting insulin secretion, suppressing appetite, and improving blood glucose regulation. The benefits stem from the exposure of undigested nutrients to different intestinal segments, which stimulates enteroendocrine activity and positively influences systemic metabolism. These hormonal adaptations contribute significantly to the metabolic improvements observed post-surgery, independent of weight loss alone. Understanding how gut structural and functional changes drive hormonal responses provides valuable insights into the mechanisms underlying the success of MBS. Moreover, elucidating these processes may facilitate the development of less invasive therapies that mimic the metabolic benefits of surgery. Ultimately, this research advances our understanding of gut-mediated regulation of energy and glucose homeostasis and holds promise for improving treatment strategies for obesity and related metabolic disorders.